Systematic Literature Review on the Effectiveness of Wayground Interactive Learning Media in Mathematics Learning - I Made Edy Bangkit Saputra; Ketut Agustini; I Gde Wawan Sudatha (Jayapangus Press, 2026)
The development of information technology has encouraged the adoption of interactive digital learning media to overcome the challenges of abstract mathematics learning and make it more concrete. This study aims to analyze the effectiveness of the Wayground platform (formerly Quizizz) as an interactive presentation medium in improving mathematics learning at the junior high school level. The research method used is a Systematic Literature Review (SLR) with the PRISMA model on 12 selected articles from 2021 to 2025. The articles discuss the effectiveness of learning media, particularly interactive or technology-based media, in the context of mathematics learning. The specific types of media include relevant interactive learning media, whether directly mentioning